ANALYSIS OF THE TRASH FROM THE CLEANING OF SEED COTTON (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article talks about a dynamic model that explains how impurities travel inside the bulk of cotton and how they are elastically connected to the cotton. Based on the parameters of the cleaning drum, patterns have been observed in the movement of the particles inside and on the surface of the cotton mass as a result of forces acting on them. The radius of the cleaning drum and the angular velocity of the drum represent the forces acting on the particle.